Natural Resistance in Populus deltoides Clones against the Defoliator Clostera cupreata in North-western India - I - Singh, Arun P.; Pandey, Rajiv (Indian Forester, 2000)
Feeding potential of the defoliator, Clostera cupreata was evaluated on 40 fast growing American clones of Populus deltoides in the laboratory to find out their resistance/susceptibility to this pest. Differences in leaf area eaten for these clones were significant (p = 0.0864). Clones were divided into 6 categories [most resistant (5 clones), moderately resistant (10 clones), marginally resistant (8 clones), marginally susceptible (7 clones), moderately susceptible (2 clones) and most susceptible (8 clones)]. Clone G-48 followed by clones S4C2 , 113413,3567 and S13C14, respectively were ranked as 'most resistant' clones. On other hand clones S7C8 followed by clones 113324, S7C1, 82-33-3, 82-36-1, ST-124, D-75 and 82-26-5 were found to be 'most susceptible'. Amongst the resistant clones, clones G-48, 3324, D-67, S7C7, 82-35-4 and A-13 showed better growth performance than other clones. Therefore, these six clones are promising for large scale plan.tation in defoliator prone areas. On the other hand clones S7C8, S7C1, S7C20, D-75, D-74, 1133'24, ST-124, 82-33-3, 82-36-1 and 82-26-5 which although have been found to be superior to clone G-3 in terms of growtb increment in field trials but are comparatively 'more susceptible' to this defoliator and should be avoided for plantation in defoliator prone areas.